Potential of Piezoelectric Floor Tile for Harvesting Energy from Human Footsteps - Nicharas Thanach-Issarasak; Subhawat Jayasvasti; Phonexai Yingyong; Don Isarakorn (My University, 2021)
Since the last decade, piezoelectric floor tile energy harvesters have been developed to convert wasted mechanical energy into usable electrical energy. Our team has also been developing and improving this kind of harvester, abbreviated as EHFT, for several years. One of the developmental problems was in reporting a realistic value of energy generated by EHFT because it depended heavily on many real-world factors. The objective of this study was to determine such realistic value by simulating those factors with a real-world traffic of 30 people entering a building. An EHFT together with proper electrical measurement devices were installed at the entrance of a building in King Mongkut's Institute of Technology, Thailand, and a group of 30 people were asked to step on it while entering the building. The value of the cumulative generated energy from the EHFT with those participants for a time duration of 600 s was found to be 450.26 mJ. This value was sufficiently high to constantly power a temperature sensor during a whole workday. Therefore, we are in the process of developing an automated Covid-19 detection station in which the temperature sensor will be powered by this EHFT.
Keywords: Innovative Energy Harvesting Technologies; Advanced Sensor and Energy Harvesting Materials; Energy Harvesting in Wireless Networks